2017
DOI: 10.1021/acs.jmedchem.7b00259
|View full text |Cite|
|
Sign up to set email alerts
|

Nitrile in the Hole: Discovery of a Small Auxiliary Pocket in Neuronal Nitric Oxide Synthase Leading to the Development of Potent and Selective 2-Aminoquinoline Inhibitors

Abstract: Neuronal nitric oxide synthase (nNOS) inhibition is a promising strategy to treat neurodegenerative disorders, but development of nNOS inhibitors is often hindered by poor pharmacokinetics. We previously developed a class of membrane-permeable 2-aminoquinoline inhibitors and later rearranged the scaffold to decrease off-target binding. However, the resulting compounds had decreased permeability, low human nNOS activity, and low selectivity versus human eNOS. In this study, 5-substituted phenyl ether-linked ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 67 publications
(174 reference statements)
3
39
1
Order By: Relevance
“…22, 24 Intermediate 27 , containing a cyanophenyl linker, was synthesized from bromophenyl precursor 22d by treatment with CuCN in DMF at 150 °C. Sonogashira coupling was then performed on 27 to install the amine tails.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…22, 24 Intermediate 27 , containing a cyanophenyl linker, was synthesized from bromophenyl precursor 22d by treatment with CuCN in DMF at 150 °C. Sonogashira coupling was then performed on 27 to install the amine tails.…”
Section: Resultsmentioning
confidence: 99%
“…Using a benzonitrile ring as the middle aromatic linker had some success in the 2-aminoquinoline- 22 and the 2-aminopyridine- 24 containing inhibitors in the past, but it showed the opposite effects with compounds 10 or 14 here. We were able to obtain the structures of rnNOS- 10 (Figure 5A) and hnNOS- 10 (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Water-mediated interactions, especially hydrogen bonds, play key roles in drug binding. 236,237 Careful examination of these water molecules and their energetics can contribute to successful drug design, as exemplified by neuronal nitric oxide synthase inhibitors, nonpeptidic urea HIV protease inhibitors and benzoxaborole non-nucleoside polymerase inhibitors of HCV. [238][239][240] Recently, several structural and computational studies to explore water-binding pockets have been reported.…”
Section: Exploring Water-binding Pockets (Structural Water Molecules) In Structure-based Designmentioning
confidence: 99%